Laying off employees expert solutions to everyday challenges. (Pocket mentor series., 2009)
Implementing a layoff is one of the most difficult and painful challenges a manager can face. Handled skillfully and compassionately, a layoff can set your team and your company on a positive new path; but, when handled improperly, layoffs can have negative effects that impact morale, productivity and more.